Big Nate : in the zone - Peirce, Lincoln (New York Harper, 2014)
"The latest illustrated novel from Lincoln Peirce is a laugh-out-loud must-read starring the one and only cartooning genius, king of detention, and Cheez Doodle connoisseur, Nate Wright. Nate's not having the best of luck . . . in fact; he's not having ANY luck. But with a little boost thanks to Chad's lucky foot, suddenly good luck is everywhere Nate turns! Nate's in the zone! But how long will it last?" --
Keywords: Middle schools -- Juvenile fiction; Schools -- Juvenile fiction; Conduct of life -- Juvenile fiction; Fortune -- Juvenile fiction; Graphic novels; Middle schools -- Fiction; Schools -- Fiction; Conduct of life -- Fiction; Luck -- Fiction